Two new species of Pseudolaguvia (Teleostei: Erethistidae) from Bangladesh - Ng, Heok Hee (Zootaxa, 2005)
Two new South Asian catfish species of the family Erethistidae, Pseudolaguvia inornata and Pseudolaguvia muricata, are described from the Brahmaputra and Feni River drainages in Bangladesh. Pseudolaguvia inornata from the Feni River drainage can be distinguished from congeners in having a uniform coloration with a pale mid-dorsal stripe and brown submarginal stripes on each lobe of the caudal fin, while P muricata from the Brahmaputra River drainage can be distinguished from congeners by its elongate dorsal and pectoral-fin spines.